As representações sociais dos educadores dos Centros Familiares de Formação em Alternância sobre Agroecologia - Leonardo de Miranda Siqueira (2020)
This thesis analyzed the ways of thinking, feeling and acting of the educators of the Family Centers of Formation in Alternation (Ceffas) in relation to agroecology, from the Theory of Social Representations. For that, the processes that generated Social Representations - anchoring and objectification - were highlighted and the elements that pressure the subjects to inference were pointed out. Regarding the research object, there was an initial assumption that there was a tension in educators between agroecology and the conventional agricultural system, agribusiness. To support this study, a theoretical framework was built about Ceffas and agroecology, in which the birth trajectory was outlined, in the Brazilian context, in the Espírito Santo context and, later, in the northern state of Espírito Santo, places of this research. The methodological approach adopted was a qualitative one, the data were collected from structured questionnaires and narrative interviews. The sample group was composed of Ceffas educators from the north of the state of Espírito Santo, 65 questionnaires and 18 narrative interviews were analyzed. The structured questionnaires served to outline the profile of the educators and the narrative interviews to have the processes of constitution of the Social Representations. The narrative interviews were submitted to content analysis based on the categories: trajectories, pressure to inference and practices. The results pointed to Social Representations of educators on agroecology in three emphases: (1) Social Representations of agroecology in the technical emphasis, with 33% of the interviewed educators; (2) Social representations of agroecology in the technical and pedagogical emphasis, with 39% of the educators interviewed; and (3) Social Representations of agroecology in the technical, pedagogical and movement emphasis, with 28% of educators interviewed. With regard to agribusiness, which was the main element of the research problem, 83% of educators pointed it out as something that put pressure on inference. Anchoring and objectification are evident in the analysis, and anchoring was presented as the subject's supports, while objectification was presented as the object's clarifying body, when the subject is able to materialize the previously abstract contents. We also demonstrated in our findings that an anchorage can have several objectives. About the representational movements, we find three types: the first movement formed by educators who have maintained their Social Representations since they joined Ceffa; the second formed by educators who are unbalanced with their representations through their experience in the context of Ceffa; and the third, formed by educators who reworked their representations, constituting new Social Representations regarding agroecology. Thus, from the analysis of the Theory of Social Representations it was possible to recognize the conflicts present in the context of these subjects and how this contributed to the elucidation of the proposed research problem.